Current Knowledge and Use of Mifepristone for Miscarriage in Utah and the Impact of An Educational Video On Future Use [A292]. (May 2022) - Kaiser, Jennifer E.; Kurtz, Theresa; Glasser, Annabah; Brintz, Ben; Turok, David; Sanders, Jessica
Abstract : INTRODUCTION: We aimed to 1) describe current use of mifepristone for miscarriage management in Utah, 2) identify predictors of knowledge pre- and post-educational video, and 3) explore post-video impacts on the likelihood to use mifepristone. METHODS: Between September 2020 and March 2021 we surveyed Utah clinicians from six specialties offering miscarriage management, recruited through professional organization and hospital listservs. Participants completed a pre-video questionnaire, viewed a 3.5-minute educational video on mifepristone for miscarriage, and completed a post-video questionnaire. We evaluated predictors of high pre-video and improved post-video knowledge using random forest regression conditional importance measures and partial dependency plots. We describe current mifepristone use and post-video effects on likelihood to use mifepristone. RESULTS: Of 530 participants, most specialize in emergency medicine (34%) and practice in private settings (51%). Most had heard of mifepristone for any indication (69%), but fewer than half knew of its use for miscarriage (42%). Of the 38% desiring mifepristone use for miscarriage, only 59% reported successful use. Baseline knowledge scores were low (mean=4.81/13 [37%] correct). Important predictors of high pre-video knowledge include prescription or attempted prescription of mifepristone, having heard of mifepristone, providing medication or expectant miscarriage management, and specialty type. Mean post-video knowledge scores improved by 67%. Low pre-video knowledge score and prior prescription or attempted prescription of mifepristone were predictive of improvement. Post-video, 64% stated they are much more or somewhat more likely to use mifepristone. CONCLUSION: Among Utah providers, baseline mifepristone knowledge and use are low. An educational video improved knowledge and likelihood of use.